USING MODIFIED SNIFFER SCRIPTS, IMPLEMENTING LINEAR ALGORITHMS FOR DETECTION OF NETWORK PORT SCAN ATTACKS IN LINUX BASED OPERATING SYSTEMS: USING MODIFIED SNIFFER SCRIPTS, IMPLEMENTING LINEAR ALGORITHMS FOR DETECTION OF NETWORK PORT SCAN ATTACKS IN LINUX BASED OPERATING SYSTEMS - Boyanov, Petar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
In this scientific paper modified sniffer scripts, implementing linear algorithms for detection of network port scan attacks in Linux based operating systems are presented.